When something is inversely proportional to another thing, when one of the numbers increases or gets multiplied by a constant, the other number decreases or gets divided by a constant.
In this scenario, when F = 3, d = 4.
When d = 2, we are dividing the earlier value of 4 by 2. Now, since F is inversely proportional to d, we have to multiply the value of F by 2 to get what F equals when d = 2. 3 times 2 is 6, so F = 6 when d = 2.
If you're evaluating, then multiply by the conjugate and simplify. = -1 -i The answer would be the same even if you divided...and or, wrote it in simplest form.